Prevalence of discontinuation of contraceptives due to failure among women aged 14 to 49 years in Uganda: a nation wide cross-sectional survey - Ruth Ketty Kisuza; Saviour Kicaber; Derrick Bary Abila; Felix Bongomin; Christopher Orach Garimoi (BMC, 2023)
Abstract Background Sustained motivation is essential for effective use of contraceptive methods by women in low- and middle-income countries as many women are likely to abandon contraceptives, especially when they continually experience episodes of failure. We aimed to determine the prevalence of discontinuation of contraceptives due to failure and its associated factors among Ugandan women aged 14-49 years. Methods A cross sectional study was conducted using the UDHS 2016 data. Multi stage stratified sampling was used to select participants. All eligible women aged 15 to 49 years at the time of the survey were enrolled. Bivariable and Multivariable logistic regression analysis were used to determine the factors associated with contraceptive failure. All analysis were done using Stata version 13. Contraceptive failure (getting pregnant while on contraceptives) within five years preceding the survey was the dependent variable. Results A total of 9061 women were included in the study. The overall prevalence of contraceptive failure was 5.6% [n = 506, 95% CI: 5.1-6.1] and was higher (6.2%) among women aged 20-29 years or had completed secondary education (6.1%). Having informed choice on contraceptives [aOR = 0.59, 95% CI: 0.49 - 0.72] and older age [aOR = 0.46, 95% CI: 0.24-0.89] were associated with lower odds of contraceptive failure. Conclusion The burden of contraceptive failure among women of reproductive age in Uganda is substantial and significantly varied by women's age, level of education, exposure to the internet, mass media, and informed choice. These findings highlight the need for improved counseling services and contraceptive quality to help women and couples use methods correctly and consistently.